Caracterização taxonômica de novos materiais da Flora Dicroidium na formação Santa Maria, triássico superior do sul do Brasil - Epifânio, Nathália Mota (2024)
Dicroidium Flora is a plant assemblage that dominated Gondwana during the Middle and Upper Triassic. Its earliest records were found in Jordan, dating back to the Permian. This flora comprises various fossil genera such as Neocalamites, Cladophlebis, Tetraptilon, Dicroidium, Ginkgoites, and Williamsonia, with the primary taxon being the genus Dicroidium. Dicroidium is documented in South Africa, Antarctica, Australia, India, the Arabian Peninsula, and South America. In South America, records come from Argentina (extensively studied), Chile, and Brazil. In Brazil, Dicroidium records began in 1952 with Gordon and Brown in the municipality of Santa Maria, in the Passo das Tropas Member, followed by systematic studies that described a diversity of plant species such as Dicroidium odontopteroides, Dicroidium zuberi, reproductive organs, as well as fish insects and conchostracans. This floristic diversity found in Santa Maria is located within a set of sandstone rocks, interlayered with mudstones, called the Passo das Tropas Member, in a site studied for many years by researchers, but which had all its outcrops buried due to the city's expansion. The materials for this dissertation were collected through a paleontological salvage during the construction of a condominium, resulting in 125 pieces with plant impressions that were cataloged at the Laboratory of Stratigraphy and Paleobiology at UFSM. Identification of the material was made with the help of the paleobotanical collection of the Museum of Geological History of Rio Grande do Sul at Unisinos. As a result, the Estância dos Montes outcrop was presented, and a stratigraphic profile was made and compared with other profiles of the Passo das Tropas Member. Subsequently, the material was identified and the species found were described. From the samples received, it was possible to identify at species level Dicroidium odontoperoides, Dicroidium zuberi, Dicroidium lancifolium, and at genus level umkomasia sp., Pteruchus sp., Neocalamites sp. This work adds information to the Passo das Tropas Member with a new outcrop, enhances the body of studies on the global Dicroidium Flora and contributes to the understanding of the South Brazilian Triassic period regarding the floristic diversity of this period.